Formula and preparation method of cellulose-based conductive humidity sensing material

By constructing a multi-network structure system of hydrogen bonding, chemical crosslinking and ion composite crosslinking, the problem of insufficient conductivity of chitosan and cellulose is solved, efficient humidity sensing and good mechanical properties are achieved, and a novel solution is provided for biomass-based flexible humidity sensors.

CN119661905AInactive Publication Date: 2025-03-21XI'AN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983144.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing humidity sensor materials mainly use synthetic polymers, resulting in environmental pollution, poor permeability and complex manufacturing processes. At the same time, the conductivity of chitosan and cellulose is not sufficient to meet the needs of electroactive sensing.

Method used

By providing a formulation of a cellulose-based conductive humidity sensing material, including cellulose, chitosan, metal salts and crosslinking agents, a multi-network structure system of hydrogen bonds, chemical crosslinking and ion composite crosslinking is constructed to improve the conductivity and mechanical properties of the material.

Benefits of technology

The effective interconnection of chitosan and cellulose is achieved, which gives the material good conductivity and humidity response performance, while improving the mechanical properties and stability of the material, providing new ideas for the design and preparation of biomass-based flexible humidity sensor film materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661905A_ABST
    Figure CN119661905A_ABST
Patent Text Reader

Abstract

The invention discloses a formula and a preparation method of a cellulose-based conductive humidity sensing material. The cellulose-based conductive humidity sensing material comprises the following components: cellulose, deionized water, an esterifying agent, a catalyst, chitosan, metal salt and a cross-linking agent, and N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide are used together; the invention also provides a preparation method of the material, which comprises the following steps: taking cellulose, adding deionized water and stirring, adding an esterifying agent and stirring, uniformly mixing and stirring with a catalyst, adjusting the pH value to be neutral, drying to obtain esterified modified cellulose, taking chitosan and a metal salt solution, mixing and stirring, adding the esterified modified cellulose into the mixture and stirring to obtain the material. A cross-linking agent is added, the pH value is adjusted to be weak acid, and a conductive humidity sensing material is obtained; chitosan and cellulose formed in the formula form a good cross-linking system, diversified influence effects are achieved, and the conductive humidity sensing film or paper with good humidity response and conductive effects can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite polymer materials and polymer material film preparation, and in particular to a formula and a preparation method of a cellulose-based conductive humidity sensing material. Background Art

[0002] Humidity sensor materials have excellent flexibility and processability, and are widely used in non-contact switches and interface positioning, smart wearable devices, environmental monitoring, respiratory monitoring, electronic skin and soft robots. Humidity sensor materials can stimulate shape change or memory recovery through moisture, water, pressure, etc., thereby achieving the perception effect of the external environment.

[0003] At present, humidity sensor materials are generally made of polymer materials. Since they are mainly synthetic polymer materials, they are not easily biodegradable and will inevitably cause environmental pollution. In addition, humidity sensors made of polymer materials also have problems such as poor permeability and complex manufacturing process.

[0004] Based on the above problems, some researchers proposed using environmentally friendly natural cellulose as a base material to prepare humidity sensor materials, mainly using chitosan and cellulose as the base material.

[0005] Chitosan (CS) is the second most abundant natural polysaccharide obtained by partial deacetylation of chitin. It has the advantages of non-toxicity, biocompatibility, antibacterial properties and good film-forming properties. It is rich in hydrophilic groups such as hydroxyl and amino groups and responds rapidly to humidity and pH. Therefore, it has great application potential in the design and development of humidity sensors; however, the processing difficulty and fragility of pure chitosan films have greatly limited their specific applications.

[0006] Cellulose is a structural polysaccharide composed of long chains of covalently linked glucose units. The base ring of the cellulose macromolecule is a macromolecular polysaccharide formed by D-glucose molecules connected by β-1,4 glycosidic bonds. Cellulose is the most widely distributed and abundant polysaccharide in nature. It is the main component of the cell walls of vascular plants, lichens and some algae, accounting for more than 50% of the carbon content in the plant kingdom. After processing, cellulose has excellent elastic modulus and mechanical strength, and is widely used as a reinforcing agent. Industrial production is also cost-effective and efficient, and it is easy to obtain.

[0007] However, with respect to conductivity requirements, the high hydrophilicity of chitosan and cellulose makes them prone to overhydration under high humidity conditions, and chitosan has an orthorhombic crystal structure composed of linear and antiparallel stacked chains of strongly hydrogen-bonded glucosamine units, while the chain spacing of cellulose molecules is very small, which severely limits ion transport. Therefore, the conductivity of chitosan and cellulose is not sufficient to meet the actual needs of electroactive sensing.

[0008] As for the conductivity problem, it is currently mainly achieved through carbonization of cellulose and chitosan, or through chemical modification or adding conductive additives (such as carbon materials, synthetic conductive polymers, metals and metal oxides, etc.), but such methods usually easily lead to insufficient interface compatibility between the matrix and the conductive filler, and reduce the mechanical properties of the composite material.

[0009] Based on the above background and problems, how to effectively interconnect chitosan and cellulose and give them conductivity, so as to prepare chitosan and cellulose-based conductive active materials with diverse and controllable properties such as good humidity response, pressure response, and good mechanical properties, has become an important technical issue to replace synthetic polymer humidity sensor film materials. Summary of the invention

[0010] The present invention aims at the potential humidity sensing applications of electroactive biomass materials such as chitosan and cellulose in contactless switches, smart wearable devices, environmental monitoring, etc., which have low electroactivity and easy hydration, and require the addition of carbon materials, synthetic conductive polymers or metal oxides, etc., and introduce a large amount of chemical cross-linking, facing the problems of poor filler matrix dispersibility, high preparation cost, and environmental pollution. First, a formula of a cellulose-based conductive humidity sensing material is provided, and the formula includes the following components in parts by weight: Cellulose: 3 to 115 parts; Deionized water: 200 to 400 parts; Esterifying agent: 24 to 920 parts; Catalyst: 3.6 to 138 parts; Chitosan: 80 to 120 parts; Metal salt: 0 to 6 parts; The crosslinking agent is N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide used together, with the weight proportion being 30 to 50 parts.

[0011] Further, the pH adjuster is one or a mixture of NaOH, KOH or NH3·H2O, with a weight ratio of 60 to 100 parts; Acetic acid or hydrochloric acid: 80 to 120 parts; Anhydrous ethanol: 30 to 50 parts.

[0012] Further, the cellulose includes one of the following two forms: (A) microcrystalline cellulose, cellulose nanofibers or a mixture thereof; (B) α-cellulose, β-cellulose or γ-cellulose, or a mixture of these.

[0013] Furthermore, the esterification agent is a carboxylic acid, and the carboxylic acid is a dicarboxylic acid, a tricarboxylic acid or an anhydride.

[0014] Furthermore, the catalyst is one or a mixture of phosphotungstic acid, hydrochloric acid or acetic anhydride.

[0015] Furthermore, the metal salt includes at least one of metal salt solutions of AlCl3, CuCl2, FeCl3, MgCl2, NaCl, CaCl2, MgSO4, CaSO4, and CuSO4.

[0016] In addition, the present invention also provides a method for preparing a cellulose-based conductive humidity sensing material, wherein the preparation method uses the above-mentioned formula and is prepared according to the following steps: S10: Preparation of esterified modified cellulose: Take the cellulose, add it to the deionized water and stir it to form a dispersion; add the esterification agent to the dispersion and stir it to form a first mixture; uniformly mix the first mixture with the catalyst and stir it to form a second mixture; adjust the pH value of the second mixture to neutral, and then dry it to obtain the esterified modified cellulose; S20: Preparation of a composite solution of chitosan-esterified modified cellulose-metal ions: The chitosan and the metal salt solution are mixed and stirred to form a chitosan metal ion complex; the esterified modified cellulose is prepared to form an esterified modified cellulose aqueous solution, which is added to the chitosan metal ion complex and stirred to form a third mixture; the cross-linking agent is added to the third mixture and stirred evenly, and the pH value is adjusted to weak acidity to obtain the chitosan-esterified modified cellulose-metal ion composite solution, i.e., the conductive humidity sensing material.

[0017] Furthermore, the preparation method also includes preparing a conductive humidity sensor membrane: preparing the composite solution of chitosan-esterified modified cellulose-metal ions by an evaporation-induced self-assembly method to form a composite film, placing it in a silicon membrane container for molding, and then drying it to form the conductive humidity sensor membrane.

[0018] Furthermore, the preparation method also includes preparing conductive humidity sensor paper, wherein the conductive humidity sensor paper is prepared by taking commercial wood pulp paper, placing it in the composite solution of chitosan-esterified modified cellulose-metal ions for one or more immersion, and then drying it to obtain the conductive humidity sensor paper.

[0019] Furthermore, the formation of the chitosan-metal ion complex further comprises: taking the chitosan and the acetic acid, uniformly mixing them to form an acetic acid-chitosan solution; taking the metal salt solution, and adding it to the acetic acid-chitosan solution under stirring to form the chitosan-metal ion complex.

[0020] The formula of the technical solution of the present invention has the characteristics of being non-toxic and having good biocompatibility, and has the characteristics of being able to form a good cross-linking system between chitosan and cellulose. The prepared conductive humidity sensing material has the characteristics of being able to be applied in a diversified form in a solution form, a direct film-forming form or an impregnated paper form, and provides a component that enables the conductive humidity sensing material to have good conductivity, and enables the conductive component to effectively form a chelate of metal ions with the chitosan and cellulose cross-linking system, thereby obtaining a material system with high stability. The preparation process utilizes the esterification reaction between citric acid and cellulose to esterify and modify the cellulose and introduce it into the chitosan matrix, and by adding a chemical cross-linking agent and Cu 2+ ions, constructed a multi-network structure system of hydrogen bonds, chemical cross-linking and ionic composite cross-linking, and prepared a composite solution of chitosan-esterified modified cellulose-metal ions (CS-EMC-Cu) system. Furthermore, the evaporation induced self-assembly method (EISA) was used to prepare a flexible conductive humidity sensing membrane (CS-EMC-Cu conductive humidity sensing membrane).

[0021] After testing and analysis, Cu 2+ The addition of ions and esterified modified cellulose effectively improves the flexibility of chitosan film, and improves the water resistance and surface hydrophilicity of chitosan. The CS-EMC-Cu conductive humidity sensing membrane has excellent humidity sensitive recovery performance, and the conductivity under dry conditions can reach 0.277S / m, and has good humidity (0.745RH -1 ) and pressure sensing performance.

[0022] Furthermore, commercial wood pulp paper was impregnated in the CS-EMC-Cu material solution system to prepare conductive humidity sensor paper (CS-EMC-Cu conductive humidity sensor paper). After testing and analysis, the CS-EMC-Cu material solution system has good compatibility with the base paper, and the composite solution can penetrate into the interior of the base paper. The CS-EMC-Cu conductive humidity sensor paper has good flexibility, and forms a good conductive effect, good water resistance, and good wet response characteristics.

[0023] The CS-EMC-Cu material solution system, CS-EMC-Cu conductive humidity sensing film and CS-EMC-Cu conductive humidity sensing paper provided in the embodiments of the present invention provide new ideas for the design and preparation of biomass-based flexible humidity sensor film materials, which is of great significance for the high added value utilization of biomass materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the present embodiment or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0025] Figure 1 A schematic diagram of the main process of preparing the conductive humidity sensing material in this embodiment; Figure 2 Surface SEM images of CS-EMC-Cu conductive humidity sensing films with different EMC contents; Figure 3 SEM images of the cross-section of CS-EMC-Cu conductive humidity sensing membranes with different EMC contents; Figure 4 Cu 2+ Effect of content on the surface morphology of CS-EMC-Cu conductive humidity sensing film SEM; Figure 5 The stress-strain curves of pure chitosan (CS) conductive humidity sensing film and conductive humidity sensing films of different component materials; Figure 6 The stress-strain curves of conductive humidity sensing films with different component materials; Figure 7 Cu 2+ The influence curve of content on stress-strain of conductive humidity sensing film; Figure 8 The deformation diagram of the conductive humidity sensing film absorbing finger sweat; Fig. 9 Schematic diagram of the homemade humidity response sensing measurement device (Ⅰ) and pressure response sensing measurement device (Ⅱ); Fig.10 This is the effect of EMC dosage on the conductivity of the conductive humidity sensor film and the brightness of the bulb; Fig.11 Cu 2+ Conductivity diagram of the conductive humidity sensing film of the content; Fig.12 Design diagram of intelligent electrical switch for conductive humidity sensing membrane; Fig.13 Experimental diagram of a smart electrical switch for a conductive humidity sensing film that opens / closes a circuit in response to humidity changes; Fig.14 The dynamic response and recovery curves of the “conductive humidity sensing film sensor” cycling between 97%RH, 52.4%RH and 33%RH.

[0026] Fig.15 This is a graph showing the change in color and surface contact angle of the conductive humidity sensor paper as the number of immersion times increases; Fig.16 The surface and cross-sectional SEM images of the conductive humidity sensing paper; Fig.17 The stress-strain curves of commercial wood pulp paper and conductive humidity sensing paper are shown in Figure 2. Fig.18 Schematic diagram of the experimental setup (Ⅰ) of connecting the conductive humidity sensor paper to the circuit under different humidity environments and the brightness of the bulb (Ⅱ); Fig.19 It is a new type of composite system material of chitosan-esterified modified cellulose-copper ion, conductive humidity sensing membrane, conductive humidity sensing paper, cross-linking reaction mechanism and the formed multi-cross-linking network structure diagram; Fig. 20 A reaction diagram for preparing esterified modified cellulose; Fig.21 Reaction diagram for preparing conductive humidity sensing material. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in this embodiment to clearly and completely describe the technical solution in this embodiment. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the present invention, the descriptions of "first", "second", etc. are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0029] This embodiment provides a formula of a cellulose composite chitosan-based conductive humidity sensor material, the components of the formula and their weight parts are: Cellulose: 5 to 15 parts; Deionized water: 200 to 400 parts; Esterifying agent: 60 to 100 parts; Catalyst: 9 to 15 parts; Chitosan: 80 to 120 parts; Metal salt: 0 to 6 parts; The crosslinking agent is N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide used together, with the weight proportion being 30 to 50 parts.

[0030] In this embodiment, the formula further includes: a pH adjuster, which is one or a mixture of NaOH, KOH or NH3·H2O, with a weight ratio of 60 to 100 parts; Acetic acid or hydrochloric acid: 80 to 120 parts; Anhydrous ethanol: 30 to 50 parts.

[0031] In this embodiment, the cellulose includes one of the following two forms: (A) microcrystalline cellulose, cellulose nanofibers or a mixture thereof; (B) α-cellulose, β-cellulose or γ-cellulose, or a mixture of these.

[0032] In this embodiment, the esterification agent is a carboxylic acid, which is a dicarboxylic acid, a tricarboxylic acid or an anhydride, preferably citric acid, oxalic acid, oxalic acid, malic acid, malonic acid or acetic anhydride, or a mixture of several thereof.

[0033] In this embodiment, the catalyst is one or a mixture of phosphotungstic acid, hydrochloric acid or acetic anhydride.

[0034] In this embodiment, the metal salt includes at least one of metal salt solutions of AlCl3, CuCl2, FeCl3, MgCl2, NaCl, CaCl2, MgSO4, CaSO4, and CuSO4.

[0035] The formula of the technical solution of the present invention is non-toxic and has good biocompatibility, and has the characteristic of being able to form a good cross-linking system between chitosan and cellulose. The prepared composite system material has diversified application characteristics in the form of solution or direct film-forming form, and provides components that make the material have good conductivity, and enables the conductive component to effectively form chelation of metal ions with the chitosan and cellulose cross-linking system, thereby obtaining a material system with high stability.

[0036] In this embodiment, some contents use English abbreviations instead of Chinese names, wherein the comparison table of English abbreviations (abbreviations of English names of compounds) and Chinese names is shown in Table 1 below.

[0037] Table 1 Comparison table of English abbreviations and Chinese names

[0038] In this embodiment, in order to analyze esterified modified cellulose (EMC) and copper ions (Cu 2+) dosage on the prepared conductive humidity sensing film, as shown in “E x C y " format is used to mark the conductive humidity sensing membranes with different components, where "E" represents esterified modified cellulose (EMC), "C" represents copper ions (Cu 2+ ), " x "and" y ” represent EMC and Cu respectively 2+ The ratio of the amount relative to chitosan (CS).

[0039] This embodiment also provides a method for preparing a cellulose composite chitosan-based conductive humidity sensor material, which is prepared using the above-mentioned formula of the cellulose composite chitosan-based conductive humidity sensor material.

[0040] One of the above formulas is selected to prepare a cellulose composite chitosan-based conductive humidity sensor material according to the composition ratio of the embodiment code E20C3 in Table 2 below. The preparation method includes the following steps: See also Figure 1 ; Figure 1 It is a schematic diagram of the main process of preparing the conductive humidity sensing material according to this embodiment.

[0041] Step S10: Preparation of esterified modified cellulose: 10 g of microcrystalline cellulose was added to the deionized water-ice water mixture, and stirred at a high speed of 16000 rpm to 20000 rpm to form a dispersion containing 10 wt % of modified cellulose.

[0042] 80 g of citric acid was added to the dispersion and stirred for 8 to 12 minutes to form a first mixture.

[0043] The first mixture was uniformly mixed with 200 mL of a 6 wt % aqueous solution of terephthalic acid, and magnetically stirred for 25 to 35 minutes. Thereafter, a homogenizer was used for shear stirring at 11,000 to 15,000 rpm for 20 minutes, and then magnetically stirred for 6 hours in an oil bath heated at 120° C. to form a second mixture.

[0044] The second mixture was treated in an ultrasonic treatment environment with a power of 100 W for 1.5 hours, after which a 0.5 mol / L NaOH aqueous solution was added and centrifuge stirring was repeated (stirring speed 7000 rpm to 9000 rpm, 10 minutes each time, 3 to 5 times in total), and an aqueous solution of a pH adjuster was added to the second mixture and centrifugally stirred to adjust the pH value to 7.0±0.5 to form a suspension.

[0045] The suspension was continuously centrifuged and stirred at a rotation speed of 4000 rpm to 6000 rpm for 5 minutes to form a supernatant liquid, and then the supernatant liquid was rotary evaporated and dried using a rotary evaporator to obtain powdered esterified modified cellulose.

[0046] Step S20: Preparation of a composite solution of chitosan-esterified modified cellulose-copper ions: 0.4 g of chitosan and 2 wt % of an acetic acid aqueous solution were taken, and the two were uniformly mixed to form an acetic acid chitosan solution with a chitosan content of 2 wt %.

[0047] Take 0.8 mg / mL CuCl2 solution, add it dropwise to the chitosan acetate solution under stirring, and stir for 24 hours to allow chitosan to complex with copper ions to form a chitosan copper ion complex.

[0048] A certain amount of esterified modified cellulose was weighed, and deionized water was added to prepare an aqueous solution with an esterified modified cellulose content of 2.5 wt %. The aqueous solution was added dropwise to the chitosan copper ion complex under stirring, and stirred continuously for 12 hours to form a third mixture.

[0049] Take 0.16g of N-hydroxysuccinimide and 0.16g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, add 5mL of anhydrous ethanol, stir and dissolve, then add to the third mixture under stirring, and continue stirring for 20 minutes, then drop an aqueous solution of a pH regulator, adjust the pH value to 6.0±0.5, stir at 60°C to react for 12 hours, and then stir at room temperature for 12 hours to obtain the chitosan-esterified modified cellulose-copper ion composite solution, that is, the conductive humidity sensing material.

[0050] The preparation method of the conductive humidity sensing material of this embodiment uses chitosan and esterified modified cellulose as the base, introduces Cu 2+ and cross-linking agents (N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide) to construct a new composite system material of chitosan-esterified modified cellulose-copper ion with a triple network structure of ionic coordination, chemical covalent cross-linking and hydrogen bond cross-linking.

[0051] Furthermore, the conductive humidity sensing film made of the conductive humidity sensing material has good conductive properties, hydrophilic properties and mechanical properties, and can be formed into a flexible humidity sensing film, an intelligent air switch film and a piezoresistive sensing film.

[0052] Furthermore, by impregnating commercial wood pulp paper in a new composite system material of chitosan-esterified modified cellulose-copper ions, a paper-based material with good conductive properties, hydrophilic properties and mechanical properties is also formed.

[0053] To further illustrate the influence of the dosage of each key component of this embodiment on the performance of the conductive humidity sensor material, the following formulations of different embodiments are provided in Table 2: Table 2 Formulation scheme of different embodiments

[0054] The EMC (wt %) in Table 2 is prepared according to the amounts of the components and weight fractions in Table 3 below.

[0055] Table 3 Preparation formula of EMC (wt%) corresponding to different embodiments

[0056] For each embodiment in Table 2, the above preparation method is also used for preparation to form each group of corresponding conductive humidity sensing materials, conductive humidity sensing films or conductive humidity sensing papers.

[0057] 1. Performance analysis of conductive humidity sensing film: In one embodiment, the respective groups of formulas of the conductive humidity sensing material in Table 2 above are further used to prepare a conductive humidity sensing membrane: the composite solution of chitosan-esterified modified cellulose-copper ions is prepared by an evaporation induced self-assembly (EISA) method to form a composite film, which is placed in a silicon film container for molding, and then dried in a vacuum oven at 45° C. to 55° C. to form a conductive humidity sensing membrane.

[0058] In order to more fully illustrate the performance of the conductive humidity sensor films prepared above, the humidity, pressure and conductivity were tested respectively; the thickness of all the film samples used for testing, comparison and analysis in the thin film state was 0.18±0.02mm.

[0059] The following is a detailed description of the test process and results: Test (1): Scanning electron microscopy (SEM) observation of the cross section and surface of conductive humidity sensing membranes made of different component materials.

[0060] The test analysis method is: The surfaces of E0C3 (chitosan copper ion complex) and CS-EMC-Cu conductive humidity sensing films of different esterified modified cellulose (E10C3, E20C3, E30C3, E40C3) were observed using a scanning electron microscope; the samples were sputter-coated with gold-palladium alloy before observation.

[0061] The test analysis results are: See also Figure 2 ; Figure 2 Surface SEM images of CS-EMC-Cu conductive humidity sensing films with different EMC contents.

[0062] It can be seen that when esterified modified cellulose (E0C3) is not added, the surface of the conductive humidity sensor membrane (E0C3) is rough and has many large cracks on the surface; this phenomenon is because chitosan is cross-linked by N-hydroxysuccinimide (NHS) and 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), Cu 2+ Chelating with -OH and -NH2 on chitosan; after adding a small amount of EMC, such as E10C3, the surface roughness of the conductive humidity sensing membrane is significantly reduced, there are small cracks and holes on the surface, and no large cracks exist, indicating that the interface compatibility of the conductive humidity sensing membrane is improved after adding EMC.

[0063] When the amount of esterified modified cellulose increases, such as E20C3 and E30C3, the surface roughness of the conductive humidity sensing membrane increases, and a large number of rod-like structures can be observed; See also Figure 3 ; Figure 3 SEM images of the cross section of CS-EMC-Cu conductive humidity sensing film with different EMC amounts.

[0064] It can be seen that when no esterified modified cellulose is added, a large number of grooves appear on the cross-section of the E0C3 conductive humidity sensing membrane, and when a small amount of esterified modified cellulose is added, the cross-sectional area of ​​the conductive humidity sensing membrane becomes flat; however, when the amount of esterified modified cellulose continues to increase, such as E20C3, a large number of voids and multi-level pores appear in the cross-section of the conductive humidity sensing membrane; compared with the E20C3 conductive humidity sensing membrane, the cross-sectional pores of the E30C3 and E40C3 conductive humidity sensing membranes are relatively reduced.

[0065] Add Cu 2+ The final test results are: See also Figure 4 ; Figure 4 Cu 2+ SEM image of the effect of content on the surface morphology of CS-EMC-Cu conductive humidity sensing film.

[0066] It can be seen that the surface of the E20C0 conductive humidity sensor film is relatively flat; when Cu 2+ When Cu is added, the surface of the conductive humidity sensor membrane becomes rough, and a large number of multi-level holes and cracks appear; the surface of the E20C4.5 conductive humidity sensor membrane has many wrinkles; 2+ Finally, the cross-section of the conductive humidity sensing film is relatively flat, but partial adhesion of strip-like structures forming a multi-level pore structure can be observed in some areas, such as the E20C3 film.

[0067] Test (2): Analysis of the mechanical properties of conductive humidity sensor membranes made of different component materials.

[0068] The test analysis method is: The mechanical properties of the conductive humidity sensing film and paper were analyzed using a universal testing machine. The conductive humidity sensing film was prepared using materials including pure chitosan (CS), chitosan-esterified modified cellulose (CS-EMC), chitosan copper ion complex (CS-Cu) and CS-EMC-Cu conductive humidity sensing films with different compositions (E10C3, E20C3, E30C3, E40C3), and was cut into 6mm×50mm strips for mechanical property testing. Each film was measured three times and the average value was taken.

[0069] The test analysis results are: See also Figure 5 ; Figure 5 The stress-strain curves of pure chitosan (CS) conductive humidity sensing film and conductive humidity sensing films with different component materials.

[0070] Pure chitosan (CS) film has a large tensile strength, but after adding crosslinker, EMC and Cu 2+ After that, the tensile strength of the conductive humidity sensing film decreased, but the toughness of the conductive humidity sensing film was significantly improved.

[0071] See also Figure 6 ; Figure 6 The stress-strain curves of conductive humidity sensing films with different component materials.

[0072] It can be seen that the ultimate tensile strength and elongation at break of the E0C3 conductive humidity sensing membrane are 2.72 MPa and 50.4%, respectively; compared with E0C3, the addition of EMC effectively improves the tensile strength and elongation at break of the conductive humidity sensing membrane; after adding a small amount of EMC, such as the conductive humidity sensing membrane E10C3, the ultimate tensile strength and elongation at break are increased to 5.28 MPa and 106.1%, respectively.

[0073] Add Cu 2+ The final test results are: See also Figure 7 ; Figure 7 Cu 2+ Content on the stress-strain curve of the conductive humidity sensing film.

[0074] Add Cu 2+ The elongation at break and toughness of the conductive humidity sensing film can be significantly improved. In the CS-EMC-Cu conductive humidity sensing film, CS and EMC interact through hydrogen bonds and covalent bonds, while Cu 2+ They form ionic complexes with the -NH2 group of CS and the -OH group of EMC respectively; cross-linking is beneficial to improving the mechanical properties, while too many cross-linking points (or too high cross-linking density) will lead to material embrittlement.

[0075] By adding CS and a small amount of Cu to esterified cellulose 2+ As a substrate, the tensile strength, elongation and modulus of the conductive humidity sensing film can be improved simultaneously; Cu in cellulose 2+ The ionic interactions between Cu and -OH groups help improve the tensile deformation without reducing the tensile stress; the additional ionic interactions help absorb energy during sample stretching; and the increase in the conductivity of the Cu in the humidity sensing film 2+ The content can effectively increase the elongation at break and also increase the tensile strength of the conductive humidity sensing film.

[0076] Cu 2+ A small increase in the dosage of Cu (such as E20C1) can simultaneously improve the tensile strength and elongation at break of the conductive humidity sensing film, but further increasing the dosage will reduce the tensile strength; by combining the ultimate tensile strength and elongation at break of the conductive humidity sensing film samples, it can be seen that the ultimate tensile strength and elongation at break of the E20C1 sample are the largest, which are 5.91MPa and 106%, respectively, and the mechanical properties of the conductive humidity sensing films of E20C4, E10C3, and E20C3 are second; therefore, Cu 2+ The addition of EMC has a significant regulatory effect on the multi-cross-linked structure of the conductive humidity sensing membrane.

[0077] Test (3): Deformation test analysis of the conductive humidity sensor film when it absorbs finger sweat.

[0078] See also Figure 8 ; Figure 8 The deformation diagram of the conductive humidity sensing film when it absorbs finger sweat.

[0079] The test analysis method is: At room temperature (ambient humidity is 52.4%RH), the conductive humidity sensing film strip is placed on the finger with tweezers. The E20C3 conductive humidity sensing film can be deformed quickly, and the bending angle of the conductive humidity sensing film reaches about 45° in about 2 seconds.

[0080] After the finger is removed, the conductive humidity sensing film spline returns to its initial state, indicating that the bending of the conductive humidity sensing film is reversible; however, when the conductive humidity sensing film is worn on a gloved finger, it remains static instead of bending and deforming, indicating that the deformation is caused by the asymmetric expansion of the conductive humidity sensing film due to the uneven absorption of water molecules by the conductive humidity sensing film.

[0081] The test analysis results are: When the surface of the E20C3 conductive humidity sensor film touches the finger, the sweat on the finger pulp will enter the conductive humidity sensor film. There are many hydrophilic groups in CS and EMC, which can form good hydrogen bonds with water molecules. CS, EMC and Cu2+ The channels generated by cross-linking facilitate the transport of water molecules, which quickly diffuse to the upper surface of the conductive humidity sensing membrane through the channels and further interact with CS and EMC through hydrogen bonds, resulting in the expansion of the contact surface volume.

[0082] However, the densely entangled EMC and CS networks in the conductive humidity sensing film and the Cu 2+ The cross-linked network formed as cross-linking points will hinder the vertical transport of water molecules to the surface.

[0083] Therefore, the lower surface of the conductive humidity sensing film absorbs more water than the upper surface, resulting in an expansion gradient and thus a stress difference between the upper and lower surfaces, which promotes the bending deformation of the conductive humidity sensing film. After removing the finger, the water molecules in the conductive humidity sensing film are rapidly desorbed into the external environment, thereby rebuilding the intermolecular hydrogen bonds between CS and EMC, generating an asymmetric contraction force, and restoring it to its original shape.

[0084] Test (4): Conductivity test analysis of the conductive humidity sensor membrane.

[0085] The test analysis method is: The conductivity of the conductive humidity sensing film surface was measured using a four-probe resistance tester. The thickness of the sample strip was first measured with an electronic caliper before testing (the probe area on the film surface was a square area of ​​2.35 mm × 2.35 mm). The surface of each composite film was tested at five different locations and the average value was taken.

[0086] Humidity sensing properties: The humidity sensing properties of the conductive humidity sensing film were measured using an electrochemical workstation.

[0087] See also Fig. 9 ; Fig. 9 Schematic diagram of the homemade humidity response sensing measurement device (I) and pressure response sensing measurement device (II).

[0088] First, use copper tape to stick two copper wires with a length of 10 cm on both ends of the composite film (10 mm × 30 mm). The copper tape serves as the electrode of the composite film. The distance between the two electrodes is 2 cm. The exposed composite film serves as the humidity sensing part, and the copper wire is connected to the electrode of the electrochemical workstation.

[0089] The humidity sensing properties of the composite film were measured by switching the composite film into a closed container in various humidity environments. Various saturated salt solutions (MgCl2-33%RH, NaBr-56%RH, NaCl-75%RH, K2SO4-97%RH) were applied to provide the humidity environment required for the test; during the measurement, the prepared sensor was placed in a humidity bottle, and when the current value was stable, the sensor was quickly switched to another humidity bottle.

[0090] See also Fig.10 ; Fig.10 This is a graph showing the effect of EMC dosage on the conductivity of the conductive humidity sensor film and the brightness of the bulb.

[0091] The conductivity of the conductive humidity sensing film was measured by a four-probe resistance tester. The conductive humidity sensing film is conductive under an ambient humidity of 52.4%RH. The conductivity of the E0C3 and E20C3 conductive humidity sensing films are 0.0425S / m and 0.1760S / m, respectively. It is worth noting that with the continuous increase of EMC content, the conductivity of the conductive humidity sensing film first increases and then decreases. When the EMC content is 30wt%, its conductivity reaches a maximum value of 0.2770S / m, which is the strongest conductivity. The trend reflected by the change in the brightness of the conductive humidity sensing film lighting LED is consistent.

[0092] As the EMC dosage increases, the interaction between CS and EMC increases, the compatibility increases, and the EMC increases. 2+ complexation to form a conductive network, thereby improving the conductivity; however, when the dosage of EMC is too high, it may cause self-aggregation of EMC, resulting in 2+ The effective sites for complexation are insufficiently reduced, which ultimately affects the conductivity of the conductive humidity sensing membrane.

[0093] Add Cu 2+ The final test results are: See also Fig.11 ; Fig.11 Cu 2+ Conductivity graph of the conductive humidity sensing film.

[0094] When Cu 2+ When the content reaches 3wt%, the maximum conductivity of the conductive humidity sensor membrane can reach 0.176S / m; under ambient humidity, the surface of the conductive humidity sensor membrane easily adsorbs water molecules.

[0095] See also Fig.12 and Fig.13 ; Fig.12 Design diagram of intelligent electrical switch for conductive humidity sensing membrane; Fig.13 Experimental diagram of a smart electrical switch with a conductive humidity sensing film that opens / closes a circuit in response to humidity changes.

[0096] In view of the good conductivity and humidity response of the conductive humidity sensing film, it can be used in the design of intelligent electrical switches.

[0097] The circuit consists of a DC power supply, a copper sheet, an electrical switch made of E20C3 film (1cm×3cm), a small light bulb, two dovetail clips, and several copper wires; specifically, one end of the conductive humidity sensing film is clamped, while the other end is in free contact with the copper sheet, thereby activating the entire circuit; when a finger approaches, the conductive humidity sensing film is bent upward by the moisture of the finger and contacts the copper sheet, thereby conducting the circuit and lighting up the LED bulb. Therefore, it is shown that the conductive humidity sensing film shell is applied to a contactless air smart switch.

[0098] Test (5): Humidity response sensing performance test of conductive humidity sensing film: The test analysis method is: Taking the initial current at room temperature and ambient humidity as the baseline, the "conductive humidity sensing membrane sensor" made of E20C3 film was placed in a 97% relative humidity environment for 10 seconds, taken out and quickly exposed to the room, and then placed in a 33% relative humidity environment for 10 seconds after the baseline stabilized, and then placed in the room again after the baseline stabilized, and then placed in a 97% relative humidity environment for 10s. The process was then cyclically tested and the response curve of the entire process was recorded by the electrochemical workstation.

[0099] See also Fig.14 ; Fig.14 The dynamic response and recovery curves of the “conductive humidity sensing film sensor” cycled between 97, 52.4 and 33% RH.

[0100] The test analysis results are: The "conductive humidity sensing film sensor" can quickly sense changes in ambient humidity; under the condition of 33%RH, the water molecules in the conductive humidity sensing film quickly escape from the film, resulting in a decrease in the conductive ions in the conductive humidity sensing film, so the response of the "conductive humidity sensing film sensor" is negative. Although the "conductive humidity sensing film sensor" is removed after 10 seconds, due to the increase in ambient humidity, water molecules are quickly adsorbed to the surface and diffuse into the interior of the "conductive humidity sensing film sensor", and the conductivity is enhanced.

[0101] By placing the "conductive humidity sensing film sensor" in a K2SO4 saturated salt solution (97%RH), as the ambient humidity further increases, more water molecules are adsorbed to the surface and diffuse into the interior of the "conductive humidity sensing film sensor", and the conductivity of the "conductive humidity sensing film sensor" is further enhanced, resulting in a positive response.

[0102] (II) Preparation and performance analysis of conductive humidity sensing paper: In one embodiment, the conductive humidity sensor paper is further prepared by using the respective formulations of the conductive humidity sensor material in Table 2 above: commercial wood pulp paper is immersed in the composite solution of chitosan-esterified modified cellulose-copper ions for several times, and then dried to obtain the conductive humidity sensor paper.

[0103] The preparation method is: In one embodiment, the above-mentioned preparation method is used to immerse commercial wood pulp paper in the above-mentioned CS-EMC-Cu system composite solution (E20C3) to prepare conductive humidity sensor paper (CS-EMC-Cu impregnated paper), and the color, surface contact angle, cross-sectional SEM, mechanical strength properties, and conductive properties are tested.

[0104] Test (1) Color change and surface contact angle change with the number of immersions.

[0105] See also Fig.15 ; Fig.15 This is a graph showing the changes in the color and surface contact angle of the conductive humidity sensor paper as the number of immersion times increases.

[0106] It can be seen that after being impregnated with the CS-EMC-Cu composite solution, the color of the conductive humidity sensing paper turns to light blue and becomes darker with increasing number of impregnation times.

[0107] Due to the small amount of sizing agent used, the surface of commercial wood pulp paper is hydrophobic with a contact angle of 107.8°; it can be seen that with the increase of the number of impregnation times, the contact angle of the surface gradually decreases. When the number of impregnation times increases from 1 to 4, the contact angles are 85.5°, 73.6°, 72.0° and 70.5°, respectively, and the electrical conductivities are 0S / m, 0.0109S / m, 0.0737S / m and 0.0801S / m, respectively. It can be seen that the hydrophilicity and conductivity of the conductive humidity sensor paper change little after three impregnations.

[0108] The following analysis is based on the conductive humidity sensor paper after three immersions.

[0109] Test (2) Cross-sectional SEM test changes of the conductive humidity sensor paper.

[0110] See also Fig.16 ; Fig.16 Surface and cross-sectional SEM images of the conductive humidity sensing paper.

[0111] Conductive humidity sensing paper after three immersions, the composite solution fills the pores of the original paper, and the roughness of the surface and cross section is reduced.

[0112] Test (3) Mechanical strength properties of conductive humidity sensor paper.

[0113] See also Fig.17 ; Fig.17 Stress-strain curves of commercial wood pulp paper and conductive humidity sensing paper.

[0114] The ultimate tensile strength of commercial wood pulp paper is relatively high, which is 32.2MPa, while the ultimate tensile strength of the conductive humidity sensor paper is significantly reduced, but the toughness of the conductive humidity sensor paper increases with the elongation at break of 7.9%, and the conductive humidity sensor paper has good bending properties.

[0115] Test (4) the conductive properties of the conductive humidity sensor paper.

[0116] See also Fig.18 ; Fig.18 Schematic diagram of the experimental setup (Ⅰ) and bulb brightness (Ⅱ) of the conductive humidity sensor paper connected to the circuit under different humidity environments.

[0117] Wood pulp paper is insulating and non-conductive when dry, while the conductive humidity sensing paper has a certain conductivity, with a conductivity of 0.0737S / m.

[0118] The brightness of the light bulb lit by the conductive humidity sensor paper connected to the circuit after three immersions increased significantly with the increase of ambient humidity, and the conductivity of the conductive humidity sensor paper also increased; therefore, the conductive humidity sensor paper also has application potential in the field of flexible humidity sensing.

[0119] The principle of the above test effect in this implementation is as follows: See also Fig.19 , Fig. 20 and Fig.21 ; Fig.19 It is a new type of composite system material of chitosan-esterified modified cellulose-copper ion, conductive humidity sensing membrane, conductive humidity sensing paper, cross-linking reaction mechanism and the formed multi-cross-linking network structure diagram; Fig. 20 A reaction diagram for preparing esterified modified cellulose; Fig.21 Reaction diagram for preparing conductive humidity sensing material.

[0120] This embodiment utilizes the esterification reaction between citric acid and cellulose to esterify and modify the cellulose and introduce it into the chitosan matrix (such as Fig. 20 As shown), by adding chemical crosslinkers and Cu 2+ ions, constructing a multi-network structure system of hydrogen bonds, chemical cross-linking and ionic composite cross-linking (such as Fig.21 as shown).

[0121] On the one hand, Cu was introduced into chitosan and esterified cellulose matrix. 2+, and chemically cross-linked, which not only gives the composite film and wood pulp paper conductivity, but also effectively avoids the problem of poor interface compatibility between the matrix and the filler; on the other hand, the flexibility and water resistance of the chitosan film and commercial wood pulp paper are improved, and both show good wet response sensing performance.

[0122] Furthermore, the preparation of the conductive humidity sensing membrane and conductive humidity sensing paper of the new composite system material of chitosan-esterified modified cellulose-copper ions is simple and environmentally friendly, which provides more possibilities for the preparation of biomass-based conductive materials and the development of sensor devices, and is of great significance for realizing the high-value utilization of biomass materials.

[0123] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A formula of a cellulose-based conductive humidity sensing material, characterized in that: The formulation includes the following components in parts by weight: Cellulose: 3 to 115 parts; Deionized water: 200 to 400 parts; Esterifying agent: 24 to 920 parts; Catalyst: 3.6 to 138 parts; Chitosan: 80 to 120 parts; Metal salt: 0 to 6 parts; The crosslinking agent is N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide used together, with the weight proportion being 30 to 50 parts.

2. The formulation according to claim 1, characterized in that The formulation also includes: pH regulator, which is one or a mixture of NaOH, KOH or NH3·H2O, with a weight ratio of 60 to 100 parts; Acetic acid or hydrochloric acid: 80 to 120 parts; Anhydrous ethanol: 30 to 50 parts.

3. The formulation according to claim 1 or 2, characterized in that The cellulose includes one of the following two forms: (A) microcrystalline cellulose, cellulose nanofibers or a mixture thereof; (B) α-cellulose, β-cellulose or γ-cellulose, or a mixture of these.

4. The formulation according to claim 1 or 2, characterized in that The esterification agent is a carboxylic acid, and the carboxylic acid is a dicarboxylic acid, a tricarboxylic acid or an anhydride.

5. The formulation according to claim 1 or 2, characterized in that The catalyst is one or a mixture of phosphotungstic acid, hydrochloric acid or acetic anhydride.

6. The formulation according to claim 1 or 2, characterized in that The metal salt includes one or a mixture of metal salt solutions of AlCl3, CuCl2, FeCl3, MgCl2, NaCl, CaCl2, MgSO4, CaSO4, and CuSO4.

7. A method for preparing a cellulose-based conductive humidity sensing material, characterized in that: The preparation method uses the formulation according to any one of claims 1 to 6 and is prepared according to the following steps: S10: Preparation of esterified modified cellulose: Taking the cellulose, adding it into the deionized water and stirring to form a dispersion; adding the esterifying agent to the dispersion and stirring to form a first mixture; uniformly mixing and stirring the first mixture and the catalyst to form a second mixture; adjusting the pH value of the second mixture to neutral, and then drying to obtain the esterified modified cellulose; S20: Preparation of a composite solution of chitosan-esterified modified cellulose-metal ions: Taking the chitosan and the metal salt solution, mixing and stirring each other to form a chitosan-metal ion complex; The esterified modified cellulose is prepared to form an esterified modified cellulose aqueous solution, and the solution is added into the chitosan metal ion complex and stirred to form a third mixture; The cross-linking agent is taken, added to the third mixture and stirred evenly, and the pH value is adjusted to weak acidity to obtain the composite solution of chitosan-esterified modified cellulose-metal ions, namely the conductive humidity sensing material.

8. The preparation method according to claim 7, characterized in that: The preparation method further comprises preparing a conductive humidity sensing film: The composite solution of chitosan-esterified modified cellulose-metal ions is prepared into a composite film by an evaporation-induced self-assembly method, placed in a silicon film container for molding, and then dried to form the conductive humidity sensing film.

9. The preparation method according to claim 7, characterized in that: The preparation method further comprises preparing conductive humidity sensor paper, The conductive humidity sensor paper is prepared by taking commercial wood pulp paper, placing it in the composite solution of chitosan-esterified modified cellulose-metal ions for one or more immersion, and then drying it to obtain the conductive humidity sensor paper.

10. The preparation method according to claim 7, characterized in that: The formation of the chitosan metal ion complex further comprises: Taking the chitosan and the acetic acid, uniformly mixing them to form an acetic acid chitosan solution; The metal salt solution is taken and added into the chitosan acetate solution under stirring conditions to form a chitosan metal ion complex.